MRI for Assessing Response to Neoadjuvant Therapy in Locally Advanced Rectal Cancer Using DCE-MR and DW-MR Data Sets: A Preliminary Report. (27th August 2015) - Petrillo, Mario; Fusco, Roberta; Catalano, Orlando; Sansone, Mario; Avallone, Antonio; Delrio, Paolo; Pecori, Biagio; Tatangelo, Fabiana; Petrillo, Antonella
Abstract : To evaluate MRI for neoadjuvant therapy response assessment in locally advanced rectal cancer (LARC) using dynamic contrast enhanced-MRI (DCE-MRI) and diffusion weighted imaging (DWI), we have compared magnetic resonance volumetry based on DCE-MRI (V (DCE)) and on DWI (V (DWI)) scans with conventional T2-weighted volumetry (V (C)) in LARC patients after neoadjuvant therapy. Twenty-nine patients with LARC underwent MR examination before and after neoadjuvant therapy. A manual segmentation was performed on DCE-MR postcontrast images, on DWI (b -value 800 s/mm 2 ), and on conventional T2-weighted images by two radiologists. DCE-MRI, DWI, and T2-weigthed volumetric changes before and after treatment were evaluated. Nonparametric sample tests, interobserver agreement, and receiver operating characteristic curve (ROC) were performed. Diagnostic performance linked to DCE-MRI volumetric change was superior to T2-w and DW-MRI volumetric changes performance (specificity 86%, sensitivity 93%, and accuracy 93%). Area Under ROC (AUC) of V (DCE) was greater than AUCs of V (C) and V (DWI) resulting in an increase of 15.6% and 11.1%, respectively. Interobserver agreement between two radiologists was 0.977, 0.864, and 0.756 for V (C), V (DCE), and V (DWI), respectively. V (DCE) seems to be a promising tool for therapy response assessment in LARC. Further studies on large series of patients are needed to refine technique and evaluate its potential value.